Identifying the Determinants of Multidimensional Inequalities of WASH Services in Pakistan - Liaqat, Aqsa; Ilyas, Muhammad; Ahmad, Ashfaq (Annals of Human and Social Sciences, 2024)
An economy’s most basic need is water accessibility. Water inequality is a major challenge facing developing countries like Pakistan today. UNICEF and WHO have developed a joint monitoring program. The WASH index is created using ten indicators that measure 6.1 and 6.2 (equal distribution of WASH services). By applying regression to the sample size 49510, this study examines factors contributing to WASH spatial disparities. Several factors influence WASH services (household head gender, household head age, household head marital status, household head education, household income, household size, family size, occupancy status, and residence place). Water, Sanitation, and Hygiene (WASH) services are more accessible to female-headed households than male-headed households. The age of the household head is positively correlated with access to WASH (Water, Sanitation, and Hygiene) services. Household heads who are unmarried or separated have less access to WASH facilities. WASH services are positively correlated with household income. Despite this, house size (number of rooms) has a significant positive impact on access to WASH services. Rural areas have fewer WASH facilities. To address these issues, gender-sensitive policies should be developed. Multi-sectoral approaches are required for implementation. Hygiene education campaigns could also enhance equitable access to WASH.